Effectiveness of language teaching methods in improving the 11th grade English competencies: a case of Nampula secondary school in Mozambique - Germito de Castro Alexandre; Peter Tsvara (International Journal of Humanities and Innovation (IJHI), 2022)
Education's language teaching techniques play a crucial part in enhancing students' linguistic competence in any given language. Assume that educators are acquainted with and aware of the elements that influence the selection of a technique for teaching and learning a language. Then, teachers may apply suitable and successful teaching strategies based on the language abilities they want to impart to their students. This research aims to evaluate the efficacy of Language Teaching Methods (LTM) in enhancing the English language skills of grade 11 students at Nampula Secondary School (NSS) in Mozambique. To evaluate the efficacy of LTM at NSS, a quantitative research strategy and descriptive study design were used. The sample comprised of eight English language instructors and 113 students. Learners were recruited using a basic random chance sampling approach, whereas instructors were recruited using a purposive sampling strategy. The examination of data used descriptive statistics. The research revealed that the English language was taught using Communicative Language Teaching (CLT) and Cognitive Code Method (CCM). Students were supposed to acquire speaking, writing, reading, and listening abilities in the English language. The LTM used to teach English at NSS was unproductive since it failed to provide the desired teaching capabilities. Teachers should employ eclecticism to foster both productive and receptive abilities in their students.